2015
DOI: 10.3390/molecules201119717
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Developing Inhibitors for Hypoxia-Inducible Factor Prolyl Hydroxylases and Their Therapeutic Implications

Abstract: Hypoxia-inducible factor (HIF) prolyl hydroxylases (PHDs) are members of the 2-oxoglutarate dependent non-heme iron dioxygenases. Due to their physiological roles in regulation of HIF-1α stability, many efforts have been focused on searching for selective PHD inhibitors to control HIF-1α levels for therapeutic applications. In this review, we first describe the structure of PHD2 as a molecular basis for structure-based drug design (SBDD) and various experimental methods developed for measuring PHD activity. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 93 publications
2
32
0
Order By: Relevance
“…K m values determined under these conditions are consistent with the ones previously published [6][7][8][9][10] and are not significantly different across all the PHD isotypes used in the present study: 0.31, 0.98, 0.66, and 0.56 μM for PHD1, 2, 3, and FIH1 respectively. In addition, we have shown that these compounds are reversible inhibitors for PHD2.…”
Section: K M For 2-og Reversibility and Mechanism Of Inhibitionsupporting
confidence: 92%
See 1 more Smart Citation
“…K m values determined under these conditions are consistent with the ones previously published [6][7][8][9][10] and are not significantly different across all the PHD isotypes used in the present study: 0.31, 0.98, 0.66, and 0.56 μM for PHD1, 2, 3, and FIH1 respectively. In addition, we have shown that these compounds are reversible inhibitors for PHD2.…”
Section: K M For 2-og Reversibility and Mechanism Of Inhibitionsupporting
confidence: 92%
“…The modulation of the activity of these enzymes could be beneficial for the treatment of a variety of diseases, therefore, a large number of PHD2 inhibitors have been developed and are now in late stage clinical trials for the treatment of anemia and chronic kidney diseases [8][9][10][11][12][13]. Several companies have reported PHD inhibitors in clinical development for the treatment of ischemia and anemia associated with chronic renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Stable HIF1α dimerizes with the constitutively expressed b subunit to activate genes with hypoxia-response elements (HREs) in their promoters (14, 15). No HIF-1-specific inhibitors currently exist, so targeting its vital transcriptional targets and the enzymes that regulate HIF-1 activity are promising ways to modulate hypoxia signaling in cancer cells (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years in-depth work has therefore been made to find PHD inhibitors by several means, such as in silico drug screening [67], combinatorial libraries [68] and high-throughput screening [69]. These efforts have led to the discovery of several compounds, four of which are currently being tested in human clinical trials [70]. …”
Section: Introductionmentioning
confidence: 99%